2011
DOI: 10.1177/1352458511405562
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal prevalence gradient of multiple sclerosis in Latin America

Abstract: Our findings suggest a latitudinal prevalence gradient of MS in Latin American countries between Panama and Argentina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 28 publications
2
37
2
2
Order By: Relevance
“…First, the low prevalence of multiple sclerosis in our series (0.3%) contrast with that reported from Europe, where this condition has a prevalence higher than 8% [5,10]. This confirms the previously reported very low prevalence of multiple sclerosis in regions near to the equator [25]. Second, we had an important number of patients with neurocysticercosis, a disease that – with only one exception [17] – has not even been mentioned in the existing published series of neurologic outpatients.…”
Section: Discussioncontrasting
confidence: 55%
“…First, the low prevalence of multiple sclerosis in our series (0.3%) contrast with that reported from Europe, where this condition has a prevalence higher than 8% [5,10]. This confirms the previously reported very low prevalence of multiple sclerosis in regions near to the equator [25]. Second, we had an important number of patients with neurocysticercosis, a disease that – with only one exception [17] – has not even been mentioned in the existing published series of neurologic outpatients.…”
Section: Discussioncontrasting
confidence: 55%
“…Despite the low reported prevalence of MS in South America in comparison with the industrialized northern countries [28,29], our data do not seem to reflect the benign MS profile previously suggested for South American patients [11,28,30,31]. …”
Section: Discussioncontrasting
confidence: 45%
“…First recognized in the early 1920s by Charles Davenport [18], it is now widely accepted that there is geographical variation in the incidence and prevalence of MS. While many studies have demonstrated an increased incidence and prevalence in regions at higher latitudes [19,20,21], other studies have found no such association [4,22,23]. A recent meta-analysis evaluating prevalence estimates from 59 countries found a statistically significant latitudinal gradient for prevalence even after age standardization and adjustment for prevalence year [24].…”
Section: Discussionmentioning
confidence: 99%